Swimming training exacerbates pathological cardiac hypertrophy in kinin B(2) receptor-deficient mice - Batista, Elice C.; Batista, Eliza C. [UNESP]; Ramalho, Joao D. S.; Reis, Felipe C. G.; Barros, Carlos C.; Moraes, Milton R.; Pesquero, Jorge L.; Bacurau, Reury F. P.; Pesquero, Joao B.; Araujo, Ronaldo C. (Elsevier B.V., 2008)
Kallikrein-kinin system exerts cardioprotective effects against pathological hypertrophy. These effects are modulated mainly via B(2) receptor activation. Chronic physical exercise can induce physiological cardiac hypertrophy characterized by normal organization of cardiac structure. Therefore, the aim of this work was to verify the influence of kinin B(2) receptor deletion on physiological hypertrophy to exercise stimulus. Animals were submitted to swimming practice for 5 min or for 60 min, 5 days a week, during 1 month and several cardiac parameters were evaluated. Results showed no significantly difference in heart weight between both groups, however an increased left ventricle weight and myocyte diameter were observed after the 60 min swimming protocol, which was more pronounced in B(2)(-/-) mice. In addition, sedentary B(2)(-/-) animals presented higher left ventricle mass when compared to wild-type (WT) mice. An increase in capillary density was observed in exercised animals, however the effect was less pronounced in B(2)(-/-) mice. Collagen, a marker of pathological hypertrophy, was increased in B(2)(-/-) mice submitted to swimming protocol, as well as left ventricular thickness, suggesting that these animals do not respond with physiological hypertrophy for this kind of exercise. In conclusion, our data suggest an important role for the kinin B(2) receptor in physiological cardiac hypertrophy. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: hypertrophy; kinin B(2) receptor; swimming